2021
DOI: 10.1177/0954405421995605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro double helical grooved tools on performance of electric discharge drilling of Ti-6Al-4V

Abstract: Machining of complex features and holes on superalloys is a topic of both industrial and academic interest. Though the demand for high aspect ratio holes on Ti-6Al-4V is high in aerospace, biomedical and chemical industries, machining the same is very challenging due to the low thermal conductivity and debris accumulation in the machining zone. The present-day methods of hole drilling by unconventional methods like Electric Discharge Machining (EDM) make use of electrodes with poor flushing capabilities. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In this aspect, a simple cylindrical tool is modified to improve flushing and machining performance. Various types of tool geometry used by researcher are foil, 10 slotted, 11,12 stepped, 13 peripheral slots, 14 bunched, 15 tubular, 16 semi-cylindrical, 17 inclined micro-slots, 18 helical slots, 19 single and double-helical, 20 and 3D printed complex profile 21 to improve machining performance. However, all the study was focused on the experimentation to enhance material removal rate and reduce tool wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, a simple cylindrical tool is modified to improve flushing and machining performance. Various types of tool geometry used by researcher are foil, 10 slotted, 11,12 stepped, 13 peripheral slots, 14 bunched, 15 tubular, 16 semi-cylindrical, 17 inclined micro-slots, 18 helical slots, 19 single and double-helical, 20 and 3D printed complex profile 21 to improve machining performance. However, all the study was focused on the experimentation to enhance material removal rate and reduce tool wear rate.…”
Section: Introductionmentioning
confidence: 99%
“…And the double spiral groove tool has better chip breaking performance. 19 Some scholars designed drill bits with stepped geometry and compared them with a conventional drill. It was found that the delamination of the step drills at low feed rates would be reduced, and the thrust and torque were reduced when using step drills.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [10] improve debris evacuation and decreased the tool electrode wear by using a helical tool electrode. Jacob et al [11] successfully fabricated a double helical grooved tool electrode and found that the double helical grooved tool electrode performed better in debris removal than the single helical grooved tool electrode. Moreover, Kumar et al [12] fabricated a series of microinclined slots on the surface of a solid cylindrical tool electrode.…”
Section: Introductionmentioning
confidence: 99%